The mechanical properties of blended cement using microwaved sewage sludge (MSSA) and eggshell powder (ESP) - Tai, Vallienetina Ejah @ Tai Siew Chin (2017)
The rapid growth of the population in the developing country leads to the increment of the production of the wastes. Besides that, it is also leads to prosper of construction industry due to the high demand of houses and buildings. Hence, construction materials such as cement are highly demand in construction industry. Huge amount of sewage sludge and eggshells being produced from year to year and need to be disposed with proper waste management. Current disposal method for both wastes through landfill caused Malaysia facing the waste management problem as we are running out of landfill site. An alternative method to dispose sewage sludge and eggshell is to utilize it as one of the construction material. The study of the possibility to turn waste into suitable construction materials in concrete production is carried out. The sewage sludge and eggshell waste are treated and used as blended cement to partially replace the cement. In this research, four different percentage of eggshell powder with 1 0% of microwaved sewage sludge ash (MSSA) were replaced with the cement in concrete production and tested by slump test, compressive strength test, flexural strength test and splitting tensile strength test. From the investigation, the results of 10% MSSA partial cement replacement with different percentage of eggshell powder has shown the increment in strength and has the potential to replace cement since the concrete strength with the blended cement are higher than the normal plain concrete.